A study of the effect of Quercus aegilops L. seed size on its propagation in Masyaf and Al-Ghab regions - حسن, نبيل; حسن علاء الدين , (Latakia University Journal -Biological Sciences Series, 2023)
region on the germination rates and seedling growth indicators in the two regions of Al-Ghab (Tahunet Al-Halawa) and Masyaf (Tair Jumla) in Hama Governorate.The results showed that the seeds of all sizes in the two sites achieved good germination rates ranging between 75% - %97, and that the size of the seeds affects the characteristics of the seedlings; Where larger seeds produce more robust seedlings, and there is a similarity in the values ​​when the effect of the site in terms of growth indicators without significant differences, with preference to the site of Tayer Jumla. The ratio of root shoot length to vegetative shoot length R/S is greater than one in all treatments, which is a positive factor.